Mucosal co-delivery of ketorolac and lidocaine using polymeric wafers for dental application - Gina S. El-Feky; Rania Farouk Abdulmaguid; Gamal M. Zayed; Rabab Kamel (Taylor & Francis Group, 2018)
The current study aimed to investigate the effectiveness of a developed sodium alginate and polyvinylpyrrolidone K-25 (PVP K-25) polymeric wafer for the co-delivery of ketorolac and lidocaine to soft tissues for healing and pain control following gingivectomy. Nine ketorolac/lidocaine lyophilized wafers were formulated and assessed for their hydration capacity, mucoadhesion ability and in vitro release profile to select the optimum system for further clinical investigation. Wafer F6 containing 2:1 sodium alginate to PVP K-25 and 10% glycerol showed optimum properties and was selected for the clinical study. Twenty patients were included in the study and the ketorolac/lidocaine wafer was assessed versus a market product. Visual pain analog was evaluated daily for the first week and wound healing index was evaluated for one week, two weeks and one month following the procedure. The developed ketorolac/lidocaine polymeric wafer proved to be an effective method of reducing pain and discomfort together with enhancing wound healing following gingivectomy.